Manufacturing uncertainty: How reproducible is the depth of cut during turning of OFHC copper? - Zhao, Junguo; Giusca, Claudiu; Goel, Saurav (EUSPEN, 2018)
Single point diamond turning (SPDT) used for micromachining has emerged as an indispensable and high-volume production manufacturing process for shaping and finishing various materials. As a preliminary testbed study, this paper investigates manufacturing uncertainty in SPDT originating from controllable and uncontrollable sources of errors. A Moore Nanotech 350 UPL SPDT machine was employed to perform repeat cutting of step heights on OFHC copper substrate at fine cutting depths in the range of 50 nm to 500 nm. The metrology was performed by a contact stylus profilometer from Taylor Hobson. While a great deal of uncertainty was observed in the results, a stark observation was that the programmed and actual depth of cuts differed less nearer at the centre of rotation of the substrate as opposed to periphery of the substrate demonstrating that the machining achieved least uncertainty nearer to the centre of rotation. A hypothesis is accordingly proposed for achieving more deterministic certainties from SPDT.
Keywords: Micromachining; diamond turning; OFHC copper; error; uncertainty